2020
DOI: 10.1021/acsomega.0c04021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chirality and Position of Lysine Conjugation in Triplex-Forming Peptide Nucleic Acids

Abstract: Conjugation with cationic lysine residues improves the biophysical and biological properties of peptide nucleic acids (PNAs). A single lysine is routinely used to improve the solubility and prevent aggregation of the neutral and hydrophobic amide backbone of PNA. Literature precedents include the attachment of lysine at either the Nor the C-terminus. Moreover, conjugation with short lysine peptides (four to eight residues) improves the cellular uptake of PNA akin to more complex cell-penetrating peptides. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
(98 reference statements)
3
7
0
Order By: Relevance
“…The M-modified PNAs had unusually high affinity for dsRNA as the binding affinity of PNA1 and PNA2 for the matched DNA hairpins (Table , rightmost column) was 41- and 13-fold lower, respectively, and similar to the stability of mismatched PNA–dsRNA triplexes. A higher affinity of PNA for dsRNA was consistent with our earlier studies ,,, and those by Nielsen and co-workers who reported that PNA sequences longer than 9-mers were required to form stable PNA–dsDNA triplexes. These results showed that M-modified PNAs were excellent triplex-forming ligands for the recognition of dsRNA.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The M-modified PNAs had unusually high affinity for dsRNA as the binding affinity of PNA1 and PNA2 for the matched DNA hairpins (Table , rightmost column) was 41- and 13-fold lower, respectively, and similar to the stability of mismatched PNA–dsRNA triplexes. A higher affinity of PNA for dsRNA was consistent with our earlier studies ,,, and those by Nielsen and co-workers who reported that PNA sequences longer than 9-mers were required to form stable PNA–dsDNA triplexes. These results showed that M-modified PNAs were excellent triplex-forming ligands for the recognition of dsRNA.…”
Section: Resultssupporting
confidence: 92%
“…Consistent with our earlier studies, 12,27,28,32 PNA forms more stable triplexes with dsRNAs than with dsDNAs. Our recent structural studies 34 suggest that this is driven by hydrogen bonding between the amide N−H of PNA backbone and nonbridging phosphate oxygens, which is favored by their matching distances in RNA but disfavored by mismatching distances in DNA.…”
Section: ■ Discussionsupporting
confidence: 92%
“…Most notably, Rozners and co‐workers reported that using 2‐aminopyridine (M), a more basic (p K a ≈6.7) heterocycle in place of natural C (p K a ≈4.5), enabled strong recognition of G–C base pairs in dsRNA at physiological pH [6a] . Further, these studies revealed that PNA bound about ten‐fold stronger to dsRNA than to dsDNA, [5–6, 8] most likely because of hydrogen bonding between PNA and RNA backbones that was not favored in DNA [9] . Most recent studies showed that M‐modified PNAs did not perform strand invasion because M did not form a Watson–Crick base pair with G, which prevented binding of M‐modified PNAs to single‐stranded DNA and RNA [6d]…”
Section: Figurementioning
confidence: 99%
“…Substitution of cytosine (p K a ∼ 4.5) with the more basic 2-aminopyridine (M, p K a ∼ 6.7) enabled strong binding of PNAs at physiologically relevant conditions, including pH 7.4 . Interestingly, binding of the M-modified PNAs to dsRNA was at least an order of magnitude stronger than to the same sequence of dsDNA. These results suggested a hypothesis that M-modified triplex-forming PNAs might sequence-specifically recognize and functionally control dsRNA in biological systems. In this Letter, we confirm this hypothesis by showing that triple-helical binding of M-modified PNA was able to inhibit the maturation of an endogenous microRNA (miRNA or miR), miR-197 in SH-SY5Y cells.…”
mentioning
confidence: 92%